New Eco-Friendly Gypsum Materials for Civil Construction - Eires, Rute; Camoes, Aires; Jalali, Said (ADVANCED MATERIALS FORUM IV, 2008)
The sustainable world's economic growth and people's life improvement greatly depend on the use of alternative products in the architecture and construction, such as industrial wastes conventionally called ``green materials{''}. This paper concerns the main results of an experimental work carried out with the objective of developing new composite materials based on gypsum and incorporating waste material as granulated cork, a by-product of cork industry, and cellulose fibres. a waste of paper industry. Such materials are intended to be used as composite boards for non structural elements of construction, such as dry walls and ceiling. Cork (bark of the plant Quercus Suber L), a substance largely produced in Portugal, is a material whose characteristics are of considerable interest for the construction industry. It is regarded as a strategic material with enormous potential by its reduced density, elasticity, compressibility; waterproof, vibration absorption, thermal and acoustic insulation efficiency \{[\}1]. During the first stage of this research work the gypsum binder and its properties Were Studied. Then, composites with mineral additions (added to increase the waterproofing and resistance) were also developed and submitted to tests to determine their physical and mechanical properties. In last stage, reinforced composites using different industrial by-products have been developed. This paper will present the properties and the manufacture methods used to produce the above mentioned eco-friendly composites that can case ways for using industrial wastes as new construction materials, with excellent inherent thermal and acoustic properties.
Keywords: Construction Technology; Cork Residue; Green materials; Sustainability; Waste recycling